KAJIAN PENDEKATAN PERANCANGAN BERBASIS KINERJADALAM PROSES PENYELENGGARAAN BANGUNAN GEDUNG - Sani Heryanto sani (NALARs, 2022)
ABSTRACT: Performance based design apporach in building delivery process is taking place from the initital stage or since the conceptual design, conducted collaboratively with multidisciplinary approach by involving all parties involved. This design approach has many advantages over traditional methods, including predicting building performance and optimizing all resources used when the building is operated by integrating building systems using simulation applications. However, this approach has not been widely practiced in the construction industry due to the sequential mannner apllied in many construction projects and the inadequate resources available. This paper attempts to convey the understanding and implementation of the performance-based design approach in building design, the problems faced and the use of simulation tools to predict and optimize the building performance.